Maximal strength training improves work economy in trained female cross-country skiers - Hoff, J.; Helgerud, J.; Wisloff, U. (Medicine & Science in Sports & Exercise, 1999)
The present study examines the hypothesis that maximal strength training improves work economy and anaerobic threshold in trained female cross-country skiers while working on a ski ergometer. It is concluded that maximal strength training in the upper-body improved the double-poling performance by improved work economy. Work economy was improved by a reduction in relative workload and time to peak force while double poling.